Colorectal cancer – adjuvant chemotherapy, and immunotherapy for advanced disease with cetuximab monotherapy, and cancer chemotherapeutic combination - Szczylik, Cezary; Szarlej-Wcisło, Katarzyna; Korniluk, Jan (Contemporary Oncology/Współczesna Onkologia, 2005)
Colorectal cancer appears to be a real challenge for modern oncology. The global morbidity and mortality represent 875 K new cases and 570 K deaths per annum, respectively. A human population affected by colorectal cancer embrances residents of the West or others but with their style of life accepted. Molecular investigations have shown the particular genes to have an influence on the development and progression of colorectal cancer, and the huge part of the cases are sporadic. However, genetic syndromes have been known in which colorectal cancer is a well-defined part. Colorectal cancer therapy is divided into two main parts, i. e. adjuvant chemotherapy and its palliative counterpart. For ages, the treatment of colorectal cancer has been based upon 5-fluorouracil and leucovorin. Therefore, there is a great need for new drugs to be used effectively in fighting the malignancy. Oxaliplatin will be offered as a new promising drug used in the adjuvant chemotherapy in patients with colorectal cancer. Palliative chemotherapy is fulfilled by usage of 5-fluorouracil and leucovorin in various regimens. New drugs in the therapy for advanced metastatic colorectal cancer will come from the basic research on the disease. Activated EGFR plays a pivotal role in the development and progression of colorectal cancer, and evidence has accumulated that the molecule is considered a negative prognostic factor. Blocking monoclonal antibodies offer a new entity to treat advanced disease in order to hamper its progression. Cetuximab is exactly this EGFR blocking monoclonal antibody used in patients after completed palliative chemotherapy becomes irinotecan-resistant. The combination of irinotecan and cetuximab has offered approximately 19-23% overall response rate, and time to progression has been noted as 4 months, and overall survival has been presented over 8 months. Cetuximab is approved in the European Union (in Poland as well) for the treatment of advanced metastatic colorectal cancer together with irinotecan as the second-line palliative therapy in patients whose colorectal cancer progressed at the time of irinotecan infusions.